2021
DOI: 10.21037/apm-20-1876
|View full text |Cite
|
Sign up to set email alerts
|

A practical nomogram from the SEER database to predict the prognosis of hepatocellular carcinoma in patients with lymph node metastasis

Abstract: Background: The presence of lymph node (LN) metastases is associated with poor survival outcomes in hepatocellular carcinoma (HCC) patients. Because of the low probability of LN metastasis, research into the prognoses of these patients is difficult. The present study developed a nomogram model to predict the prognosis of HCC patients with LN metastasis. Methods: This retrospective, noninterventional study enrolled patients from the Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Different from intrahepatic cholangiocarcinoma and combined hepatocellular-cholangiocarcinoma (CHC), LNM represents a rare but equally aggressive biological behavior of HCC, secondary only to the lung as the destination that most commonly develops extrahepatic metastasis (9,29,30). The incidence of LNM varies in different clinical observational studies, from 1.2% to 15.3% (10)(11)(12)(13)(14)(15)(16)(17). Some possible confounding factors that could explain such a 10-fold variety were shown as follows: First, several researchers enrolled patients with fibrolamellar carcinoma even CHC, leading to an inappropriate increase in the overall LNM incidence.…”
Section: Development and Validation Of A Model To Predict Regional Ly...mentioning
confidence: 99%
See 3 more Smart Citations
“…Different from intrahepatic cholangiocarcinoma and combined hepatocellular-cholangiocarcinoma (CHC), LNM represents a rare but equally aggressive biological behavior of HCC, secondary only to the lung as the destination that most commonly develops extrahepatic metastasis (9,29,30). The incidence of LNM varies in different clinical observational studies, from 1.2% to 15.3% (10)(11)(12)(13)(14)(15)(16)(17). Some possible confounding factors that could explain such a 10-fold variety were shown as follows: First, several researchers enrolled patients with fibrolamellar carcinoma even CHC, leading to an inappropriate increase in the overall LNM incidence.…”
Section: Development and Validation Of A Model To Predict Regional Ly...mentioning
confidence: 99%
“…Overall, routine LND in HCC patients is not widely accepted by hepatobiliary surgeons in current clinical practice. Some previous studies advocated routine LND for benefits in outcome improvement, complication prevention, and comprehensive evaluation, but some others hold the opposite opinions (10,11,(23)(24)(25). Wu et al conducted a prospective randomized controlled clinical trial and concluded that LND was safe but could not improve HCC patients' prognoses.…”
Section: Development and Validation Of A Model To Predict Regional Ly...mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the heterogeneity of hepatocellular carcinoma, it is difficult to evaluate the patient prognosis. In recent years, a variety of methods have been used to evaluate the prognosis, among which the nomogram has been widely used in clinical evaluation and improves prognosis assessment (7,8). The nomogram is a graphical description of the predictive statistical model for a single patient (9).…”
Section: Introductionmentioning
confidence: 99%